Smart Shopper – Grocery Ingredient Filtering with Augmented Reality - Yap, Pei Pei (2021)
Groceries shopping is essential for most of the individual in their daily life. However, there is a wide range of similar products located on the shelf in the supermarket. People often spend a lot of time in the supermarket in reading the ingredient list on the nutrition facts label to choose the best product they want. Despite time-consuming, the main obstacle for shopper especially who are allergic to certain ingredient is they having difficulties to filter and search for the products that are perfectly free from all allergic ingredients. Hence, a smart shopper mobile application with ingredient filtering function using AR technology is proposed to improve the groceries shopping. The proposed application has the ability in assisting the user to filter and personalise the ingredient that user desire. In this development, AR technology is implemented in this project in the form of marker-based AR. By using marker-based detection, an actual object can be detected by scanning with a smartphone camera, then, the ingredient list in the virtual form will be displayed on top of the object. The project also provided a function that allowed a user to differentiate products with colour tags. Users can compare the products by just checking the checkbox of allergic ingredient. Also, this project intends to develop an Android platform mobile application which is free-of-charge to let users enjoy convenience and affordable mobile application. In comparison to previous work, a head-mounted device which is extremely expensive is required in order to experience a smart shopper with AR technology. Therefore, this project is beneficial to an individual who wishes to make groceries shopping with affordable AR experience.